2022
DOI: 10.1088/1361-6668/ac925c
|View full text |Cite
|
Sign up to set email alerts
|

Analytical approximations for the self-field distribution of a superconducting tape between iron cores

Abstract: Magnetic switches apply AC magnetic fields to DC current-carrying high temperature superconducting (HTS) tapes to generate DC voltages and are commonly used in the persistent current switches (PCSs) and flux pumps to charge HTS-coated conductor magnets. Normally, they are made of copper field coils and iron cores with narrow air gaps for the HTS tape to pass through. However, the perpendicular components of the self-field of the HTS tape in the air gap can be enhanced by the iron cores and cause a critical cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…This indicates that it is the iron core that causes the observed suppression and asymmetry and not any mechanical damage to the HTS wire. These results were repeated consistently across three different samples, confirming the analytical results in [27].…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…This indicates that it is the iron core that causes the observed suppression and asymmetry and not any mechanical damage to the HTS wire. These results were repeated consistently across three different samples, confirming the analytical results in [27].…”
Section: Resultssupporting
confidence: 78%
“…It has recently been reported that the self-field I c of an HTS wire in the air gap of an iron-core electromagnet is suppressed by almost 50% [27]. In this study, we build upon this work by empirically measuring the J c (B) characteristic of an HTS wire in the air gap of an iron-core electromagnet in liquid nitrogen (LN 2 ).…”
Section: Introductionmentioning
confidence: 97%
“…However, during the magnetisation, the heat produced by PFM will hinder the realisation of the full trapped field and flux potential in CCs [40]. While zero field cooling and flux pumping have also been reported as general magnetisation methods for CCs [41][42][43][44][45][46], they have not been employed extensively in superconducting machines.…”
Section: Introductionmentioning
confidence: 99%
“…A number of these HTS switches and FPs have the configuration of placing a HTS wire in a narrow airgap of a C-shaped iron-core magnet [2,7,12,35]. However, the selffield critical current of the single CC within the iron-core air gap is suppressed by approximately 45%, which directly influences the switching performance and efficiency [7,12,40]. On the other hand, a bifilar stack of two antiparallel REBCO CCs was used as the switching element, which is preferable for gapped-iron-core-based HTS PCSs and HTS FPs.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a bifilar stack of two antiparallel REBCO CCs was used as the switching element, which is preferable for gapped-iron-core-based HTS PCSs and HTS FPs. Such a 'noninductive' structure of bifilar stacks effectively minimizes the self-induction of the switch and substantially increases the self-field critical current of the CC, which provides more stable load fields and significantly improves the efficiency of HTS switches and FPs [1,7,12,40].…”
Section: Introductionmentioning
confidence: 99%